Jeremiah/Lamentations - Dearman, J. Andrew (Grand Rapids, MI Zondervan, 2002)
Includes bibiographial references and indexes.
Keywords: Bible. O.T. Jeremiah -- commentaries; Bible. O.T. Lamentations -- commentaries